Interleukin-6 as a critical inflammatory marker for early diagnosis of surgical site infection after spine surgery: research - Roch, Paul; Ecker, Carolin; Jäckle, Katharina; Meier, Marc-Pascal; Reinhold, Maximilian; Klockner, Friederike Sophie; Lehmann, Wolfgang; Weiser, Lukas (Infection, 2024)
Early diagnosis of surgical site infections (SSIs) could prevent surgical revision. Inflammatory markers (IMs), such as procalcitonin (PCT), interleukin-6 (IL-6), and tumor necrosis factor α (TNF-α), seem more accurate in diagnosing SSI than C-reactive protein (CRP) and white blood cell (WBC) count. The aim was to compare the predictive values of CRP, WBC count, PCT, IL-6, and TNF-α in SSI detection.